A comparison of reactivating and therapeutic efficacy of newly-developed oximes (K156, K203) and commonly used oximes (obidoxime, HI-6) in cyclosarin-poisoned rats and mice - Kassa, Jiri; Karasova, Jana Zdarova; Musilek, Kamil; Kuca, Kamil (Toxicology mechanisms and methods, 2009)
A potency of newly-developed oximes (K156, K203) and commonly used oximes (obidoxime, HI-6) to reactivate cyclosarin-inhibited acetylcholinesterase and to reduce cyclosarin-induced acute toxic effects was evaluated in this study. In vivo determined percentage of reactivation of cyclosarin-inhibited blood and tissue acetylcholinesterase in poisoned rats showed that the potency of a newly-developed oxime (K203) to reactivate cyclosarin-inhibited acetylcholinesterase and to reduce the acute lethal effects of cyclosarin, corresponding to the relatively low reactivating and therapeutic efficacy of obidoxime. The potency of another newly-developed oxime (K156) to counteract the inhibitory and acute clinical effects of cyclosarin is almost negligible. On the other hand, the oxime HI-6 is a very efficient reactivator of cyclosarin-inhibited acetylcholinesterase in the peripheral (blood, diaphragm) as well as central (brain) compartment, and it is able to reduce the acute toxicity of cyclosarin more than three times. Although the reactivating and therapeutic efficacy of the oxime K203 is higher compared to another newly-developed oxime K156, the reactivating and therapeutic potency of both newly-developed oximes is significantly lower in comparison with the oxime HI-6 and, therefore, none of them is suitable for replacement of HI-6 in the case of the treatment of cyclosarin poisoning.
Keywords: oximy; Organophosphate Poisoning; Oximes; organofosforové sloučeniny; krysa rodu Rattus; otrava organofosfáty; zvířata; myši; potkani Wistar; Mice; Rats, Wistar; Male; Acetylcholinesterase; Organophosphorus Compounds; reaktivátory cholinesterasy; Cholinesterase Reactivators; Rats; Animals; mužské pohlaví; acetylcholinesterasa